STUDI PEMBUATAN MINUMAN ISOTONIK BERBAHAN BAKU AIR KELAPA TUA (COCOS NICIFERA L) DAN EKSTRAK BELIMBING WULUH (AVVERHOA BILIMBI L) MENGGUNAKAN METODE STERILISASI NON-THERMAL SELAMA PENYIMPANAN: (Study Of Making Isotonic Drinks Based Raw Old Coconut Water (Cocos nucifera L) And Extract Of Star fruit (Avverhoa bilimbi L) By Using Sterilization non-Thermal For Storage) - Jumriah Langkong; Nandi K Sukendar; Zulfikar Ihsan (Hasanuddin University Food Science and Technology Study Program, 2018)
Isotonic drinks is one type of beverages that serves to replace body fluids lost due to physical activity. The drink is made from raw materials of coconut water and extract ”wuluh” starfruit with the addition of sugar. Coconut water used from an optimally mature of coconut and young “wuluh” starfruit. The material formulation was conducted with coconut water as much as 88%, extract “wuluh” starfruit 5%, and the addition of sugar as much as 7%. Isotonic beverage was prepared by extracting “wuluh” starfruit and preparing coconut before mixing all ingredients. The treatment was filtering using by micro filter (0.5 and 0.1 micron) and without filtering. The mixing process of the material was carried out hygienically to obtain a viable product. Based on product visualization testing by using a filter tool can longer than without a filter tool.